Paul Tschetter: the story of a Hutterite immigrant leader, pioneer, and pastor - Janzen, Rod A. (Princeton theological monographs series, 2009)
Introduction: Paul Tschetter , the Hutterite Joshua -- The Hutterites -- Growing up in Ukraine -- The journey to North America -- Immigration -- A new life in Dakota territory -- Paul Tschetter and the Hutterite colonies -- Leading the Neu Hutterthaler Church -- The evangelical alternative -- The final years -- The legacy of Paul Tschetter